1997
DOI: 10.1111/j.1530-0277.1997.tb04482.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Ethanol and the Fos Response: A Comparison of the C57BL/6J and DBA/2J Inbred Mouse Strains

Abstract: The effect of ethanol (0.25 to 4 g/kg) on the number of Fos-like immunoreactive (Fos-li) neurons was studied in the C57BL/6J (B6) and DBA/2J (D2) inbred mouse strains. The brain regions emphasized in the analysis were from the basal ganglia and some associated limbic nuclei. The question addressed was whether or not the D2 and B6 strains differed in these regions in a way that could explain the marked psychomotor stimulation of the D2, but not the B6, strain over the dose range of 1 to 2 g/kg of ethanol. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
49
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 61 publications
9
49
4
1
Order By: Relevance
“…The finding that rats will self-administer ethanol directly into VTA provides compelling evidence that this brain site is importantly involved in mediating ethanol's reinforcing effects (Gatto et al, 1994;Rodd et al, 2004). Thus, despite the lack of a direct ethanol effect on FOS expression in the VTA of DBA/2J mice (Hitzemann and Hitzemann, 1997), our finding of conditioned FOS increases in this brain area appears consistent with many other findings implicating this area in the mediation of ethanol's primary reinforcing effects. Involvement of the VTA in ethanol-induced conditioning is also consistent with findings from several studies suggesting that this brain area plays an important role in place preference conditioning induced by other abused drugs (Gholami et al, 2003;Harris and Aston-Jones, 2003;Neumaier et al, 2002;Popik and Kolasiewicz, 1999).…”
Section: Conditioned Changes In Fossupporting
confidence: 80%
See 3 more Smart Citations
“…The finding that rats will self-administer ethanol directly into VTA provides compelling evidence that this brain site is importantly involved in mediating ethanol's reinforcing effects (Gatto et al, 1994;Rodd et al, 2004). Thus, despite the lack of a direct ethanol effect on FOS expression in the VTA of DBA/2J mice (Hitzemann and Hitzemann, 1997), our finding of conditioned FOS increases in this brain area appears consistent with many other findings implicating this area in the mediation of ethanol's primary reinforcing effects. Involvement of the VTA in ethanol-induced conditioning is also consistent with findings from several studies suggesting that this brain area plays an important role in place preference conditioning induced by other abused drugs (Gholami et al, 2003;Harris and Aston-Jones, 2003;Neumaier et al, 2002;Popik and Kolasiewicz, 1999).…”
Section: Conditioned Changes In Fossupporting
confidence: 80%
“…The present studies also found that an ethanol-paired CS+ acquired the ability to induce FOS in several brain areas that have previously been reported to be unaffected by acute or chronic ethanol exposure in DBA/2J mice (VTA: Hitzemann and Hitzemann, 1997;La, CA1, CA2, DG: Ryabinin and Wang, 1998). The conditioned FOS response in VTAant, which was significant in both experiments, is of particular interest given the previously reported sensitivity of VTA dopamine neurons to direct activation by ethanol as measured by extracellular single unit recordings in a mouse brain slice preparation (Brodie, 2002;Brodie and Appel, 2000).…”
Section: Conditioned Changes In Fossupporting
confidence: 57%
See 2 more Smart Citations
“…Over the past several years, c-Fos immunohistochemistry has been used to identify neuronal sites activated by ethanol administration. Ethanol-induced c-Fos-like immunoreactivity (cFLI) has been identified in several forebrain regions that include the bed nucleus of the stria terminalis, the paraventricular nucleus of the thalamus and hypothalamus, the central nucleus of the amygdala, and the nucleus accumbens (Chang et al, 1995;Hitzemann and Hitzemann, 1997;Ryabinin et al, 1997;Thiele et al, 1998b;Zoeller and Fletcher, 1994). In the brainstem, ethanolinduced cFLI has been observed in regions that include the lateral parabrachial nucleus (PBN), the area postrema (AP), the locus coeruleus (LC), and the nucleus of the solitary tract (NTS) (Ryabinin et al, 1997;Thiele et al, 1996Thiele et al, , 1997Thiele et al, , 1998b.…”
mentioning
confidence: 99%